Evaluation of Bacteriophage Cocktail on Septicemia Caused by Colistin-Resistant Klebsiella pneumoniae in Mice Model - Singh, Aprajita; Singh, Alakh Narayan; Rathor, Nisha; Chaudhry, Rama; Singh, Sudhir Kumar; Nath, Gopal (Frontiers in Pharmacology, 2022)
Objective: The emergence of resistance against last-resort antibiotics, carbapenem and colistin-resistant in Klebsiella pneumoniae has been reported across the globe. Bacteriophage therapy seems to be one of the most promising alternatives. This study aimed to optimize the quantity and frequency of bacteriophage cocktail dosage/s required to eradicate the Klebsiella pneumoniae bacteria in immunocompetent septicaemic mice. Methods: The three most active phages ɸKpBHU4, ɸKpBHU7 and ɸKpBHU14 characterized by molecular and TEM analysis constituted in the form of cocktail and was given intraperitoneally to mice model after inducing the septicaemia mice model with the constant dose of 8 × 107 CFU/mouse Klebsiella pneumoniae. After that, the efficacy of the phage cocktail was analyzed at different dosages, i.e., in increasing, variable, constant and repeated dosage. Further, Interleukin - 6 and endotoxin levels were estimated with variable doses of phage cocktail. Results: We have elucidated that Phage therapy is effective against the Klebsiella pneumoniae septicaemia mice model and a promising alternative to antibiotic treatments. Our work delineates that a single dose of phage cocktail with 1 × 105 PFU/mouse protects the mice from fatal outcomes at any stage of septicemia. However, the higher phage dosage of 1012 PFU/mice is fatal when given at the early hours of septicemia, while this high dose is not fatal at the late stages of septicemia. Moreover, multiple repeated dosages are required to eradicate the bacteria from peripheral blood. In addition, the IL-6 levels in the 1 × 105 PFU/mouse group remain lower, but in 1 × 1012 PFU/mouse group remains high at all points, which were associated with fatal outcomes. Conclusion: Our study showed that the optimized relatively lower and multiple dosages of phage cocktails with the strict monitoring of vitals in clinical settings may cure septicaemia caused by MDR bacteria with different severity of infection.